Hypertension, antihypertensive treatment and cancer incidence and mortality: a pooled collaborative analysis of 12 Australian and New Zealand cohorts. Issue 1 (January 2016) - Harding, Jessica L.; Sooriyakumaran, Manoshayini; Anstey, Kaarin J.; Adams, Robert; Balkau, Beverley; Brennan-Olsen, Sharon; Briffa, Tom; Davis, Timothy M.E.; Davis, Wendy A.; Dobson, Annette; Giles, Graham G.; Grant, Janet; et al.
Abstract : Background: Observational studies examining associations between hypertension and cancer are inconsistent. We explored the association of hypertension, graded hypertension and antihypertensive treatment with cancer incidence and mortality. Method: Eighty-six thousand five hundred and ninety-three participants from the Australian and New Zealand Diabetes and Cancer Collaboration were linked to the National Death Index and Australian Cancer Database. Cox proportional hazards models estimated hazard ratios and 95% confidence intervals (95% CI) for the association of treated and untreated hypertension with cancer incidence and mortality. Results: Over a median follow-up of 15.1 years, 12 070 incident and 4350 fatal cancers were identified. Untreated and treated hypertension, compared with normotension, were associated with an increased risk for cancer incidence [hazard ratio 1.06, 95% CI (1.00–1.11) and 1.09 (1.02–1.16) respectively], and cancer mortality (1.07, 0.98–1.18) and (1.15, 1.03–1.28), respectively. When compared with untreated hypertension, treated hypertension did not have a significantly greater risk for cancer incidence (1.03, 0.97–1.10) or mortality (1.07, 0.97–1.19). A significant dose–response relationship was observed between graded hypertension and cancer incidence and mortality; P trend  = 0.053 and P trend  = 0.001, respectively. When stratified by treatment status, these relationships remained significant in untreated, but not in treated, hypertension. Conclusion: Hypertension, both treated and untreated, is associated with a modest increased risk for cancer incidence and mortality. Similar risks in treated and untreated hypertension suggest that the increased cancer risk is not explained by the use of antihypertensive treatment. Abstract : Supplemental Digital Content is available in the text